Sfida dentro il San Giusto - Bernardini, Fulvio (GEOmedia, 2013)
The planning of sustainable mobility is one of the exercises that for claim has entered on the agenda of European municipalities . Reduce air pollution and the use of cars and to provide citizens more efficient movements, limit traffic congestion and degradation of urban areas; these and other aspects are the guidelines on which are standardizing the major cities of the old continent. Trieste, an Italian city over 200,000 inhabitants located in the north-eastern border of the peninsula, is historically a bridge between Western and the south-central Europe. Trieste is one of the city that is better incorporating the needs of sustainable mobility, thanks to its central European character. In 2010, the Municipality of Trieste has embarked on the construction of the Park San Giusto, a futuristic solution for the parking of cars: once completed, it will be the largest park in the cave in Italy and the second in Europe, the cars will be a total of 718 on 5 levels buried beneath the hill of San Giusto , in the historic center of Trieste.